(untitled) (American Journal of Islam and Society, 2012)
In Southeast Asia and elsewhere in the Muslim world, academic institutions – particularly in the humanities and social sciences – often ignore the potential leadership role of women. This is especially evident in Islamic studies, where women play a minor role in research, teaching, and course management. Generally speaking unlike in the Middle East, many public and private Southeast Asian schools of higher learning, as well as “Islamic” schools, feature female Muslim scholars in their administrational structures. Indonesia boasts several woman serving as leaders in Islamic educational organizations, and Masnon Ibrahim is the current rector of Brunei’s Seri Begawan Religious Teachers University College. On the international level, Zaleha Kamaruddin, the recently appointed rector of the International Islamic University Malaysia (IIUM), remains the world’s first and only female rector of an Islamic institution of higher learning. This short article seeks to address her feelings, style, and role, as well the challenges in managing an international Islamic institution. It is based on her written answers to written questions, a recent unstructured interview, and personal contact gained while working together as administrators at IIUM during the 1990s.